Adipose tissue, aging, and metabolism. (March 2019) - Yu, Panxi; Yuan, Rong; Yang, Xiaonan; Qi, Zuoliang
Abstract: Adipose tissue is the largest dynamic organ system involved in energy storage as well as endocrine and immunological functions and, therefore, plays an important role in regulating aging and longevity. During aging, adipose tissue undergoes dramatic changes in mass, distribution, cellular composition, secretory profiles, and insulin responsiveness, leading to adipose tissue dysfunction. These changes, including the ectopic lipid deposition, accumulation of senescent cells, infiltration of immune cells, and increased secretion of proinflammatory cytokines and chemokines, not only have secondary physiological effects on a variety of organs, leading to multiorgan dysfunction and disability, but also importantly link with metabolic dysfunction and chronic low-grade systemic inflammation known as 'inflamm-aging, ' which can be further exacerbated by age-related obesity. Adipose tissue is also frequently involved in bariatric surgeries and plastic and reconstructive surgeries. These intimate relationships make therapeutic targeting of adipose tissue an attractive approach for combating metabolic diseases, improving life quality, and extending lifespan.